ДЕТАЛИЗАЦИЯ КРИТЕРИЕВ ЭФФЕКТИВНОСТИ РАБОТЫ ПРЕДПРИЯТИЙ В СФЕРЕ МЕЖДУНАРОДНЫХ ГРУЗОВЫХ ПЕРЕВОЗОК НА БАЗЕ СИСТЕМЫ СБАЛАНСИРОВАННЫХ ПОКАЗАТЕЛЕЙ (International Journal of Innovative Technologies in Economy, 2018)
The necessity of using a system of balanced indicators as a modern tool for ensuring the effective operation of international freight carriers is substantiated. The logic of using the balanced scorecard system is achieved by achieving certain financial results (the "Finance" projection) by taking into account the needs of the target segments (the "Customers" projection), ensuring maximum value for customers with the minimum possible costs (the "Internal business processes" projection) and having a motivated personnel with relevant qualifications (projection "Training and career growth (staff)"). A generalizing strategic goal of the work of road transport enterprises providing international cargo transportation services has been formed. The key strategic sub-goals for the development of road transport enterprises on the projects "finance", "customers", "internal business processes", "training and career growth (personnel)" are highlighted. Indicators for assessing the achievement of the goals set, their measurement units, periodicity and control conditions are detailed. The importance of the use of information technologies for the introduction of a system of balanced indicators in the work of road transport enterprises is disclosed.